2010
DOI: 10.1152/jn.00164.2010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short-Interval Intracortical Inhibition on Short-Interval Intracortical Facilitation in Human Primary Motor Cortex

Abstract: Using the paired-pulse paradigm, transcranial magnetic stimulation (TMS) has revealed much about the human primary motor cortex (M1). A preceding subthreshold conditioning stimulus (CS) inhibits the excitability of the motor cortex, which is named short-interval intracortical inhibition (SICI). In contrast, facilitation is observed when the first pulse (S1) is followed by a second one at threshold (S2), named short-interval intracortical facilitation (SICF). SICI and SICF have been considered to be mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
5
23
1
Order By: Relevance
“…First, the modulation of SICF was observed when S2 intensity was 1.0 AMT for FDI, but not 1.4 AMT. Our results, as well as other reports (Chen and Garg 2000;Shirota et al 2010), showed that higher S2 intensity produced larger SICF. Therefore, enhancement of SICF might be blurred by large peaks of SICF when S2 intensity was as high as 1.4 AMT, possibly because of modest influence of the SMA stimulation on SICF system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, the modulation of SICF was observed when S2 intensity was 1.0 AMT for FDI, but not 1.4 AMT. Our results, as well as other reports (Chen and Garg 2000;Shirota et al 2010), showed that higher S2 intensity produced larger SICF. Therefore, enhancement of SICF might be blurred by large peaks of SICF when S2 intensity was as high as 1.4 AMT, possibly because of modest influence of the SMA stimulation on SICF system.…”
Section: Discussionsupporting
confidence: 92%
“…2. As previously reported, higher S2 intensity yielded more facilitation (Chen and Garg 2000;Shirota et al 2010). Statistically, three-way repeated-measures ANOVA revealed significant main effect of S2 Intensity (F 1,12 = 25.4, p \ 0.001), ISI (F 2.8,33 = 14.1, p \ 0.001), and their interaction (F 7,84 = 3.5, p = 0.002).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This, in turn, makes it unlikely that the inhibition at ISI of 3 ms is due to refractory corticospinal axons and/or after hyperpolarization in the cell body. The inhibition is evoked especially in I3-wave at ISIs 3-5 s (Hanajima et al, 2003;Shirota et al, 2010). Based on these earlier investigations the observed latency change in our study at ISI of 3 ms may be associated with suppression of I3-waves.…”
Section: Discussionsupporting
confidence: 81%
“…The first and later SICF peaks are affected differently by manipulation of TMS stimulus parameters, indicating different underlying physiological processes [13]. SICF 1.5 is thought to result from S2-evoked excitation of the initial axonal segments of excitatory interneurons that were subliminally excited by S1, whereas SICF 2.5 and later peaks are thought to result from summation of excitatory synaptic activity [14].…”
Section: Discussionmentioning
confidence: 99%